Effect of Cultivars and Herbicides on Weed Growth and Yield of Boro Rice (Oryza sativa L.) - Kumar, Pramod; Singh, Yashwant; Singh, U. P. (International Journal of Bio-resource and Stress Management, 2023)
The field experiment was conducted during the boro seasons of 2008-09 and 2009-10 on clay loam soil of Agricultural Research Farm at Banaras Hindu University (BHU) campus, Varanasi, India to test the efficacy of herbicides under different boro rice cultivars. All the herbicidal treatments were significantly superior to unweeded control. Weed count and dry matter under ‘Prabhat’ was lower than that with other two cultivars, viz. ‘Gautam and ‘Krishna Hamsa’. Weed control efficiency with ‘Prabhat’ was higher than other two cultivars. Significantly higher grain yield of 4149.07 kg ha-1 was obtained in ‘Gautam’ cultivar. Pretilachlor @ 1.0 kg (pre emergence) fb (followed by) azimsulfuron @ 35 g a.i. ha-1 at 15 DAT with grain yield of 4353.51 kg ha-1 was significantly superior to ethoxysulfuron @ 18 g ai ha-1+fenoxaprop @ 56 g ai ha-1 at 15 DAT as well as pyrazosulfuron @ 20 g ai ha-1 (pre-emergence) fb bispyribac @ 25 g ai ha-1 at 25 DAT and was statistically similar to hand weeding twice at 30 and 50 DAT. Among herbicidal treatments, the maximum weed control efficiency of 62.87% and 63.37% in pretilachlor fb azimsulfuron and 84.02% in ethoxysufuron+fenoxaprop were recorded for broad leaved, grasses and sedges, respectively. ‘Gautam’ cultivar with highest net return of ` 24898.94 ha-1 and benefit cost ratio of 1.19 and pretilachlor fb azimsulfuron with net return of ` 27461.32 ha-1 and benefit cost ratio of 1.32 were most profitable among cultivars and herbicidal treatments, respectively.